COVID-19 pandemic: disease impact on nervous system, cognitive functioning and mental health - Janeczek, Piotr (Journal of Education, Health and Sport, 2022)
Introduction and purpose: COVID-19, as an unknown disease until 2019, has posed and continues to pose a great challenge to the world of science and the people facing it. The purpose of this article is to present the possible consequences of experiencing COVID-19 disease and the pandemic itself in light of mental health and the organism functioning in the cognitive area, taking into account the impact of COVID-19 on the nervous system. State of knowledge (brief description): Coronaviruses are enveloped, positive single-stranded large RNA viruses. COVID-19 is a disease caused by the SARS-CoV-2 virus – its first case was reported in 2019 in Wuhan, China. Human coronaviruses can exhibit neuroinvasive, neurotropic and neurovirulent, SARS-CoV-2 also. In addition to symptoms and complications in the respiratory system, symptoms and complications are also encountered in the nervous system area; cognitive functioning may also be impaired. The pandemic as a phenomenon in itself and the outbreak of COVID-19 can carry very serious consequences from the mental health field. Among these are the problem of social isolation and its consequences or the impact of the disease and pandemic on well-being. Unfortunately, the time that has elapsed since the first cases of the disease and the amount of research does not allow a clear determination of the complications and consequences of the pandemic, but certain trends and phenomena are regularly studied and described. Summary: Existing research and the state of the art strongly underscore that COVID-19 and its pandemic could impinge on the mental health of people around the world. Changes in the nervous system and cognitive functioning are also observed as a result of contracting COVID-19. Science currently has no clear answers as to how long certain complications will persist and exactly what their genesis is – further research is recommended to explain them as precisely as possible.